Blended Teaching Mode of Art Course based on Objective Achievement Scale - He, Guanyu (International Journal of Emerging Technologies in Learning (iJET), 2020)
To solve the problems of students’ lack of initiative, inadequacy in research on teaching theories, and imperfection of curriculum evaluation system in the teaching of art course, a new blended teaching mode was built in this study by extracting the advantages of Team-Based Learning (TBL), Problem-Based Learning (PBL) and Case-Based Learning (CBL) in accordance with the teaching characteristics of art course and students’ cognitive competence. This mode is designed to focus on teamwork, problem orientation and case analysis in teaching link. This teaching mode consists of online and offline modules, via which teacher releases course materials and assigns classroom tasks and students read the course materials and fulfill tasks online, and students make report on study in the form of group and teacher gives feedback and evaluations offline. An objective achievement scale model with five educational objectives set on the basis of Borich Needs Assessment Model (BNAM) was designed based on development planning and teaching orientation of art course, socio-economic development and job requirements and questionnaire survey on graduates. The conclusion shows that the blended teaching model performs better than conventional teaching model in improving students’ academic performance and promoting class enthusiasm and satisfaction with course. With the objective achievement scale model, quantitative evaluation of teaching efficiency can be realized from point, line and plane perspectives, facilitating educators in customizing proper student training program.